2012
DOI: 10.1007/s12262-012-0631-4
|View full text |Cite
|
Sign up to set email alerts
|

Value of Serum Procalcitonin in Evaluating the Prognosis of Sepsis in Elderly Patients with Colorectal Cancer Undergoing Emergency Colorectal Surgery

Abstract: Serum procalcitonin (PCT) levels may have predictive value in the prognosis of postoperative sepsis in elderly patients who have undergone colorectal surgery for colorectal cancer in intensive care units (ICUs). A prospective study involving 90 critically ill patients who underwent colorectal surgery for colorectal cancer in ICUs was performed. Twenty-eight patients were diagnosed with sepsis, in accordance with the American College of Chest Physicians/Society of Critical Care Medicine consensus criteria, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…IL-6 is the major stimulant in CRP synthesis during acute-phase responses [26]. The maximum IL-6 plasma levels precede the maximal concentrations of PCT, suggesting that the synthesis of PCT might be induced by IL-6.…”
Section: Inflammatory Proteins Cytokines and Pismentioning
confidence: 99%
“…IL-6 is the major stimulant in CRP synthesis during acute-phase responses [26]. The maximum IL-6 plasma levels precede the maximal concentrations of PCT, suggesting that the synthesis of PCT might be induced by IL-6.…”
Section: Inflammatory Proteins Cytokines and Pismentioning
confidence: 99%
“…Because PCT concentrations can be periodically elevated after operation, its measurement postoperatively can improve patient management and can be helpful in prediction of serious infections, only when the range of PCT concentrations are followed up. 26 , 27 Picariello et al 28 reported that PCT concentrations measured at the time of admission to the cardiac critical care unit have been elevated in patients with cardiogenic shock in the presence of multiple organ failure and in the absence of signs of infections (PCT levels ≥1.0 ng/mL). In survivors, a progressive reduction in PCT values was observed, whereas the lack of changes in PCT concentrations was documented in those who died.…”
Section: Pct In Different Inflammatory Conditionsmentioning
confidence: 99%
“…In the literature the cut-off for a definition of elderly varies from being either 65 or 75 years of age. Many studies define as “elderly” only patients older than 80 years [10, 11, 12, 13, 14, 15]. At present, the WHO still consider as elderly those individuals of 60 years or over; however most scientific societies define patients as elderly if their age is 65 year or more.…”
Section: Discussionmentioning
confidence: 99%